Strengthening Character In The Teaching Campus Program At The Jaya Negara Elementary School, City Of Makassar - Suardi Suardi; Syahban Nur (Universitas of Muhammadiyah Makassar, 2022)
The Independent Learning Activity-Independent Campus (MBKM) is the success of national education and a forum for character strengthening for students. This type of research is descriptive qualitative research through a case study approach. The research instrument is the researcher himself conducts interviews, observations, and documentation. The data collected is then analyzed through data reduction, data presentation, and concluding. Validation of the data is done through technical triangulation. The results of the study show that Merdeka Learning-Independence Campus (MBKM) helps the teaching and learning process at the elementary school level by involving students in the teaching and learning process, providing strengthening of the character of students such as the character of reading, critical reasoning, social care, cooperation, curiosity and disciplined character.Kegiatan Merdeka Belajar-Kampus Merdeka (MBKM) bukan hanya mensukseskan pendidikan nasional namun juga sebagai wadah penguatan karakter untuk peserta didik. Jenis penelitian adalah penelitian deskriptif kualitatif melalui pendekatan studi kasus. Instrumen penelitian adalah peneliti sendiri melakukan wawancara, observasi dan dokumentasi. Data yang dikumpulkan kemudian dianalisis melalui tahapan reduksi data, penyajian data, menarik kesimpulan. Pengabsahan data dilakukan melalui triangulasi teknik. Hasil penelitian menunjukan Merdeka Belajar-Kampus Merdeka (MBKM) membantu proses belajar mengajar di jenjang sekolah dasar dengan melibatkan mahasiswa dalam proses belajar mengajar memberikan penguatan terhadap karakter peserta didik seperti karakter gemar membaca, bernalar kritis, peduli sosial, gotong royong, rasa ingin tahu dan karakter disiplin.